2019
DOI: 10.1590/s1677-5538.ibju.2018.0724
|View full text |Cite
|
Sign up to set email alerts
|

A census of laparoscopic and robotic urological practice: a survey of minimally invasive surgery department of the Brazilian Society of Urology

Abstract: Minimally invasive urologic surgery has been developing in Brazil and now is a routine part of care in many regions and patients with different conditions benefit from it. Training in laparoscopic and robotic surgery has evolved and concerns exist both over the quality of surgical training and the practical effect on results of the urological training. This is an unprecedented study which undertook a census to determinate the current state of laparoscopic and robotic urological practice and to know the mains b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The preferred training method among respondents was a short duration hands‐on course, which is consistent with their current professional situation and offers a faster and practical way to learn. Surgical simulation models and cadaveric laboratories have been increasingly used for medical training 3 . A study evaluated residents' performance before and after a MUS teaching session that included interactive teaching stations (cadaver pelvis, retropubic MUS pelvic model, and cystoscopy model) 19 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The preferred training method among respondents was a short duration hands‐on course, which is consistent with their current professional situation and offers a faster and practical way to learn. Surgical simulation models and cadaveric laboratories have been increasingly used for medical training 3 . A study evaluated residents' performance before and after a MUS teaching session that included interactive teaching stations (cadaver pelvis, retropubic MUS pelvic model, and cystoscopy model) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most broad medical specialties have diversified into subspecialties and urology has followed this trend. The concept of sub‐specialization is based on excelling in an area of interest and it has been shown that subspecialized practice helps in improving outcomes in urology 1–5 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations